Effects of Pulsed Electromagnetic Fields on Post-operative Pain in Patients with Fresh Fracture - Yadollahpour, Dr. Ali (Asian Journal of Pharmaceutics (AJP), 2017)
Background and Objective: Pulsed electromagnetic fields (PEMFs) have shown therapeutic outcomes in bone and wound repair and pain and edema reduction. This study was aimed to investigate the effectiveness of PEMFs on post-operative pain in the patients with fresh fracture. Method: This open-label clinical trial was conducted on 20 patients with tibial and femoral fresh fractures. The patients were treated with surgery and received PEMF therapy undergoing a protocol with 20 Hz and 4.25 mT for 4 weeks (20 min daily and 5 consecutive days per week and for 4 consecutive weeks). A visual analog scale was used for recording pain. Results: During the first day of treatment patients had low pain during rest, activity, and nighttime. Each treatment session significantly reduced the mean pain score (P = 0.05). We observed a cumulative pain reduction effect where on day 4 the pain score was significantly reduced compared with day 0 (95.1 Â± 2 mm on day 0 to 46.5 Â± 3 mm on day 4) (P = 0.001). Furthermore, during the 2 days each week with no treatment session, the pain score increased to the early values. It indicated the temporary effect of PEMF on pain which lasted about 12 h posttreatment. Conclusion: PEMF showed significant clinical value in reducing the pain of post-operative pain in fracture patients. However, it seems that this effect is temporary and does not last more than 24 h after the treatment session.